The Effect of Filler Substitution on the Mechanical Properties and Morphology of CR/NR Composite - hesty eka mayasari; agung yanuar wirapraja (Jurnal Teknologi Proses dan Inovasi Industri, 2021)
Filler is one of the most important additives in making rubber goods. Filler can improve the properties of rubber goods. This study aims to determine the effect of filler substitution on the chloroprene/natural rubber (CR/NR) composite. The filler used in this study are carbon black (CB) N330, combination of zeolite and CB (1:1), combination of kaolinite and CB (1:1), and combination of bentonite and CB (1:1). The composites were done by a two-roll mill and hydraulic press. The mechanical properties and the morphology of CR/NR composite were studied using tensile strength tester and scanning electron microscope. The elemental composition of the composite was studied by X-ray fluorescence. From the study, it is known that the carbon black as a single filler gives the highest tensile strength and tear strength. The zeolite as substitute filler gives the highest tensile strength and elongation. The bentonite as substitute filler gives the lowest tensile strength and tear strength. All of the composites show fine dispersion in SEM micrograph. Zeolite as substitute filler is a potential alternative filler for CR/NR composite